TINJAUAN YURIDIS PASAL 345 KUHP MENGENAI TINDAKAN MENDORONG ORANG LAIN UNTUK BUNUH DIRI: TINJAUAN YURIDIS PASAL 345 KUHP MENGENAI TINDAKAN MENDORONG ORANG LAIN UNTUK BUNUH DIRI - Anak Agung Linda Cantika, Anak Agung Linda Cantika; I Kadek Agus Merta Adnyana (Judge : Jurnal Hukum, 2024)
The qualification for the act of ending one's own life or suicide in the criminal code is stipulated in Article 345 of the Criminal Code, stating: "Whoever deliberately encourages another person to commit suicide, assists him in the act, shall be punished with imprisonment for 4 years, if that person commits suicide." There is a blurring in the phrase "encouraging others" to commit suicide. Based on this, the formulation of the problem is: how does the regulation of criminal acts encourage others to commit suicide? and what is the legal certainty of encouraging others to commit suicide under Article 345 of the Criminal Code? This type of research is normative legal research, using statutory approaches and concepts. The legal materials used are primary, secondary, and tertiary legal materials. Legal material analysis techniques with analytical descriptive. The result of this study is that anyone who intentionally encourages another person to commit suicide, assists him in committing the act, or provides the means for it, can be punished if the act leads to death or attempted suicide. The provisions of the article create legal uncertainty, especially the blurring of norms related to the interpretation of the phrase "encouraging others" to commit suicide. What counts as "pushing" can be varied and subjective.